استخدام طريقة المفاصل اللدنة المحسّنة من المرتبة الثانية في التحليل اللدن للإطارات المستوية - محمود سعيد; نبيل دبانة; غدير هيكل (Tishreen University, 2019)
يتطلب التصميم بالطرق الحدية الحديثة دراسة السلوك اللدن للعناصر الإنشائية بعد حد الخضوع وذلك بهدف الاستثمار الأمثل لقدرة هذه العناصر في مقاومة أشكال التحميل المختلفة التي يمكن أن تتعرض لها المنشأة الهندسية. مما دعا إلى تطوير طرق التحليل الإنشائي، وبشكل خاص طريقة العناصر المنتهية، باتجاه التحليل اللدن. وتتميز طريقة المفاصل اللدنة المحسّنة من المرتبة الثانية بكونها تنمذج السلوك اللدن اللاخطي للعناصر والجمل الإنشائية بشكل فعّال. بالإضافة إلى ذلك فهي سهلة البرمجة ولا تتطلب جهداً عددياً كبيراً. سوف نقوم في هذه المقالة بشرح الأساس النظري لهذه الطريقة، بدءاً من المعادلة التي تحكم السلوك التوازني لعنصر جائز-عمود وحتى الوصول إلى علاقة الصلابة اللدنة لعنصر إطاري مستوي. ثم ننتقل لعرض المخطط النهجي الذي قدمناه لإدراج الطريقة المقترحة في برنامج تحليل إنشائي FEAW7 . أخيراً يتم حل مثال عملي تطبيقي ومقارنة النتائج مع نتائج الحل التقليدي. Modern design codes require the study of the inelastic behavior of structural elements after yielding point. That is in order to achieve the optimum investment of a member's strength and stiffness in resisting the various types of loading the structure may be subjected to. This trend resulted in the development of structural analysis methods, and particularly the Finite Elements method towards plastic analysis. The second order refined plastic hinge method offers an effective approach in modeling the inelastic structural behavior. In addition, its mathematical model can be programmed without implying high computational cost and effort. In this paper, the theory of the second order refined plastic hinge method is exposed, starting from the equation governing the equilibrium of a column-beam member, until the inelastic stiffness relationship of a plane frame element is reached. Follows the algorithm we presented for the implementation of the mentioned method in a structural analysis program, FEAW7. Finally, an example is solved to demonstrate the accuracy and effectiveness of the program on one hand, and for the comparison of the results on the other.